(untitled) (Revista Argentina de Musicología, 2021)
Efforts to codify and institutionalize tango music have emerged only recently, with tango music education programs, music schools and school curricula, instrumental methods books, tango music theory treatises, and other codifying projects developing over the past decades in Argentina and elsewhere. This article focuses on one spectacular instance of this larger trend: Tango Para Músicos/1er Encuentro Internacional, a week-long, intensive tango music education workshop that took place in Buenos Aires, Argentina from July 21-27, 2014. Drawing upon ethnographic data gathered before, during, and after the first edition of TPM in 2014, my goal here is to show how music education projects like TPM do not simply reproduce musical genres as already existing frames for cultural practice and meaning but literally make them, and make them towards particular, productive ends. Considering TPM from this perspective, I argue that the “total social fact” of music is not just “a conduit for other forms of interaction” but a productive force in its own right.